2011
DOI: 10.1016/j.chb.2010.05.011
|View full text |Cite
|
Sign up to set email alerts
|

An expertise reversal effect of segmentation in learning from animated worked-out examples

Abstract: Many animations impose a high cognitive load due to the transience of information, which often hampers learning. Segmentation, that is presenting animations in pieces (i.e., segments), has been proposed as a means to reduce this high cognitive load. The expertise reversal effect shows, however, that design measures that have a positive effect on cognitive load and learning for students with lower levels of prior knowledge, might not be effective, or might even have a negative effect on cognitive load and learn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
72
1
7

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 127 publications
(87 citation statements)
references
References 30 publications
4
72
1
7
Order By: Relevance
“…In addition, the paused materials led to significantly higher scores on a transfer test. Similar findings favoring pauses have been reported in other empirical studies (e.g., Hasler et al 2007;Hassanabadi et al 2011;Spanjers et al 2012;Spanjers et al 2011).…”
Section: Demonstration-based-training (Dbt)supporting
confidence: 79%
“…In addition, the paused materials led to significantly higher scores on a transfer test. Similar findings favoring pauses have been reported in other empirical studies (e.g., Hasler et al 2007;Hassanabadi et al 2011;Spanjers et al 2012;Spanjers et al 2011).…”
Section: Demonstration-based-training (Dbt)supporting
confidence: 79%
“…Ayres (2006) separated the expansion of two polynomial expressions into four calculations, and found that students who used the segmented materials made fewer errors and rated the task easier. Spanjers, Wouters, van Gog, and van Merriënboer (2011) achieved similar results by segmenting animated examples of working out problems. Both studies observed an expertise reversal effect when students were given segmented learning materials.…”
Section: Instructional Design: Reducing Difficulties In Learning Matesupporting
confidence: 52%
“…The findings of Boucheix and Guignard (2005) and Spanjers et al (2010) show that students with higher levels of prior knowledge do not need additional guidance through segmentation. For students with higher levels of prior knowledge, the amount of cognitive resources they can devote to cognitive activities with a positive effect on learning is reduced when they have to reconcile the instructional guidance with the guidance given by their available cognitive schemas (Kalyuga 2007).…”
Section: Enhancing Perception Of the Underlying Structurementioning
confidence: 85%
“…In the study by Spanjers et al (2010), segmentation was not combined with learner control. They investigated the effects of segmented and non-segmented animations on probability calculation procedures, and their segmented animations automatically paused after each segment and automatically continued after 2 s. A significant interaction was found between the effects of segmentation and prior knowledge: Students with lower levels of prior knowledge learned more efficiently from segmented animations than from nonsegmented animations, while students with higher levels of prior knowledge learned equally efficiently from non-segmented and segmented ones (i.e., an expertise reversal effect; Kalyuga 2007).…”
mentioning
confidence: 99%
See 1 more Smart Citation